PTFE prepreg and preparation method thereof, and copper-clad plate based on prepreg
By grafting polar acrylate monomers onto the surface of PTFE prepreg, the problem of poor adhesion between PTFE material and copper foil was solved, and a high-adhesion PTFE copper-clad laminate was prepared, which is suitable for the 5G communication field.
Patent Information
- Application Number
- CN202411590971.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
AI Technical Summary
The poor bonding strength between existing PTFE materials and copper foil leads to abnormal signal transmission in the 5G communication field, affecting its rapid promotion and widespread application.
High-bonding-strength PTFE copper-clad laminates are prepared by grafting polar acrylate monomers onto the surface of PTFE prepreg using electron beam irradiation technology to enhance their adhesion to copper foil.
It significantly improves the adhesion of PTFE copper clad laminates while maintaining the dielectric properties, making it suitable for 5G communication applications.
Smart Images

Figure BDA0005125581880000051 
Figure BDA0005125581880000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 5G communication materials, and in particular to a PTFE prepreg with high bonding strength, a PTFE copper-clad laminate, a preparation method and applications thereof. Background Art
[0002] 5G communication not only has large data and exponentially increased transmission speed, but also integrates into the network (such as the Internet of Things, Internet of Vehicles, artificial intelligence, interactive multimedia, etc.), which has greatly broadened the scope of related applications. The essence of 5G communication is high-frequency and large-capacity signal processing and transmission. The first task is to select suitable copper clad laminate (CCL) materials, which must meet the requirements of high-frequency (millimeter wave) signal transmission speed and low transmission loss, that is, the dielectric constant (DK) and dielectric loss (DF) should be as low as possible.
[0003] Currently, the CCL materials that can be used for high-frequency and high-speed signal transmission in the 5G communication field mainly include: (1) polytetrafluoroethylene (PTFE); (2) hydrocarbon resins; (3) thermosetting resins (including modified polyimide, etc.); (4) special resin (or film) materials; (5) modified (or multifunctional) epoxy resins. Among them, PTFE CCL materials have the best DK and DF as well as other superior properties, and are the most preferred materials in the 5G communication field.
[0004] PTFE is a completely symmetrical, unbranched linear polymer with high CF bond energy (460KJ / mol) and fluorine atoms densely distributed on the surface of the CC main chain, which makes the surface of PTFE material extremely chemically inert and extremely low surface energy. After the PTFE material and copper foil are pressed together in the conventional way, the bonding force between the copper foil and the PTFE material is very poor. In the subsequent PCB manufacturing process and terminal product evaluation and testing process, the copper foil and PTFE material are prone to micro-cracks or shedding abnormalities, resulting in abnormal signal transmission, which seriously affects the rapid promotion and widespread application of PTFE materials in the 5G communication industry. Summary of the invention
[0005] In view of the above problems existing in the prior art, the applicant of the present invention provides a PTFE prepreg with high bonding strength, a PTFE copper-clad laminate, and a preparation method and application thereof.
[0006] The present invention grafts polar acrylate monomers onto the surface of a PTFE prepreg through electron beam (EB) irradiation technology, and then places it between two copper foils and puts them into a hot press for pressing. The resulting copper clad laminate has greatly improved bonding strength, meeting the PCB manufacturing process requirements and terminal product testing and evaluation requirements, and is suitable for 5G communication fields such as the Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia.
[0007] The first aspect of the present application is to provide a PTFE prepreg with high bonding strength, wherein polar acrylate monomers are grafted onto the surface of the PTFE prepreg by electron beam (EB) irradiation technology;
[0008] Furthermore, the polar acrylate monomer is selected from one or more of acrylate monomers having cyano, carboxyl, hydroxyl, acetylamino, alkoxy, amino, mercapto and heterocyclic structures.
[0009] Furthermore, the polar acrylate monomer is preferably one or more of a hydroxyalkyl acrylate monomer, an alkoxylated acrylate monomer and an acrylate monomer with a heterocyclic structure.
[0010] Furthermore, the hydroxyalkyl acrylate monomer is selected from one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate and 4-hydroxybutyl acrylate;
[0011] Furthermore, the alkoxylated acrylate monomer is selected from one or more of 2-methoxy 2-acrylate, ethoxyethoxyethyl acrylate, methoxy polyethylene glycol monoacrylate, methoxy polyethylene glycol methacrylate and alkoxylated nonylphenol acrylate;
[0012] Furthermore, the acrylate monomer with a heterocyclic structure is selected from one or more of tetrahydrofuran acrylate, 2-phenoxyethyl acrylate, (2-ethyl-2-methyl-1,3-dioxolan-4-yl) acrylate and acryloylmorpholine.
[0013] The second aspect of the present application is to provide a method for preparing the PTFE prepreg with high bonding strength, comprising the steps of:
[0014] S11. After the glass fiber is arranged in the PTFE emulsion and impregnated, it is taken out and dried at high temperature to obtain a PTFE prepreg;
[0015] S12. The PTFE prepreg obtained in step S11 is immersed in a polar acrylate monomer for 3-5 minutes, and then subjected to electron beam irradiation grafting to obtain a PTFE prepreg with high bonding strength.
[0016] In some embodiments, in step S11, the solid content of the PTFE emulsion is 40-60%;
[0017] In some embodiments, in step S11, the drying temperature is 220-280° C., and the drying time is 15-30 minutes.
[0018] In some embodiments, in step S11, the impregnation time is 3-5 minutes.
[0019] Furthermore, in step S12, the electron beam irradiation conditions are: voltage 10KeV-100KeV, and dose 10KGy-100KGy.
[0020] In some embodiments, in step S12, the impregnation time is 3-5 minutes.
[0021] In some preferred embodiments, in step S11, the glass fiber cloth is electronic grade glass fiber cloth with a specification of 106.
[0022] The third aspect of the present application provides a method for preparing a copper-clad laminate based on the PTFE prepreg; comprising the steps of:
[0023] S21. The multilayer PTFE prepreg is stacked together, copper foil is placed on top and bottom, and vacuum hot pressed;
[0024] S22. After the process of step S21 is completed, the PTFE copper-clad substrate with high bonding strength is obtained by cooling down and releasing the pressure and then taking it out. In some embodiments, the PTFE copper-clad substrate with high bonding strength is obtained by naturally cooling down to room temperature and releasing the pressure and then taking it out.
[0025] In some preferred embodiments, in step S21, four PTFE prepregs are stacked together, and a RTF 1oz copper foil is placed on each of the top and bottom, and then placed in a vacuum high temperature press for hot pressing.
[0026] In some preferred embodiments, in step S21, the hot pressing conditions are as follows: vacuum degree ≥ 720 mmHg, heating rate 1.5-3°C / min, pressure 80-150 psi during heating, maximum temperature 350-400°C, maximum pressure 350-450 psi, and heat and pressure holding time 120-180 minutes.
[0027] The fourth aspect of the present application provides a copper clad laminate produced based on the production method described above.
[0028] The fifth aspect of the present application provides the application of the semi-cured sheet or the copper clad laminate in the field of 5G communications, including but not limited to applications in the fields of the Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia.
[0029] Beneficial effects: The beneficial effects of this application are at least:
[0030] The present invention grafts polar acrylate monomers onto the surface of a PTFE prepreg by electron beam (EB) irradiation technology, so that the low surface energy PTFE surface is grafted with polar groups, which greatly improves the bonding strength between the PTFE surface and the copper foil, while the dielectric properties of the PTFE material are not changed, thereby preparing a PTFE prepreg and a PTFE copper-clad laminate with high bonding strength;
[0031] The PTFE copper-clad laminate based on the PTFE semi-cured sheet provided in the present application has high peel strength (15lb / inch), extremely low dielectric constant DK@10GHz (2.22) and extremely low dielectric loss DF@10GHz (0.001), and excellent high temperature resistance (T288 60 minutes); it is suitable for 5G communication fields such as the Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Performance testing method:
[0034] 1. Peel strength test
[0035] The peel strength test of the samples prepared in the examples and comparative examples was performed with reference to IPC-TM-650 2.4.8;
[0036] 2. Dielectric constant and dielectric loss test
[0037] The dielectric constant and dielectric loss of the samples prepared in the examples and comparative examples were tested with reference to IPC-TM-650 2.5.17.1;
[0038] 3. High temperature resistance test
[0039] The samples prepared in the embodiments and comparative examples were tested for high temperature resistance according to IPC-TM-650 2.4.24.1.
[0040] The present invention is described in detail below.
[0041] Example 1
[0042] A method for preparing a PTFE prepreg with high bonding strength, the preparation method comprising the following steps:
[0043] S11: placing an electronic grade glass fiber cloth with a specification of 106 in a PTFE emulsion with a solid content of 50% for 4 minutes, taking it out and drying it in an oven at 250 degrees for 20 minutes to obtain a PTFE prepreg with a solid content of 90%;
[0044] S12: After the PTFE semi-cured sheet prepared in step S11 is immersed in 2-hydroxypropyl acrylate (HPA) monomer for 4 minutes, it is taken out and placed in an electron beam (EB) device for irradiation grafting (EB irradiation conditions: voltage 70KeV, dose 30KGy) to obtain a PTFE semi-cured sheet with high bonding strength.
[0045] A method for preparing a PTFE copper-clad laminate with high bonding strength, the method comprising the following steps:
[0046] S21: stack the four PTFE prepregs prepared in step S12 together, place a Luxembourg HFZ-B copper foil on each side, and place them in a vacuum high-temperature press for hot pressing (pressing parameters: vacuum degree greater than 720 mmHg, heating rate 2.0 degrees / minute, pressure during heating process 120 psi, maximum temperature 375 degrees, maximum pressure 400 psi, heat and pressure holding time 150 minutes);
[0047] S22: After the process of step S21 is completed, the temperature is naturally lowered to room temperature and then the pressure is released and taken out to prepare a PTFE copper-clad substrate with high bonding strength.
[0048] Example 2
[0049] A method for preparing a PTFE prepreg with high bonding strength, the preparation method comprising the following steps:
[0050] S11: placing an electronic grade glass fiber cloth with a specification of 106 in a PTFE emulsion with a solid content of 50% for 4 minutes, taking it out and drying it in an oven at 250 degrees for 20 minutes to obtain a PTFE prepreg with a solid content of 90%;
[0051] S12: After the PTFE semi-cured sheet prepared in step S11 is immersed in ethoxyethoxyethyl acrylate (EOEOEA) monomer for 4 minutes, it is taken out and placed in an electron beam (EB) device for irradiation grafting (EB irradiation conditions: voltage 70KeV, dose 30KGy) to obtain a PTFE semi-cured sheet with high bonding strength.
[0052] A method for preparing a PTFE copper-clad laminate with high bonding strength, the method comprising the following steps:
[0053] S21: stack the four PTFE prepregs prepared in step S12 together, place a Luxembourg HFZ-B copper foil on each side, and place them in a vacuum high-temperature press for hot pressing (pressing parameters: vacuum degree greater than 720 mmHg, heating rate 2.0 degrees / minute, pressure during heating process 120 psi, maximum temperature 375 degrees, maximum pressure 400 psi, heat and pressure holding time 150 minutes);
[0054] S22: After the process of step S21 is completed, the temperature is naturally lowered to room temperature and then the pressure is released and taken out to prepare a PTFE copper-clad substrate with high bonding strength.
[0055] Example 3
[0056] A method for preparing a PTFE prepreg with high bonding strength, the preparation method comprising the following steps:
[0057] S11: placing an electronic grade glass fiber cloth with a specification of 106 in a PTFE emulsion with a solid content of 50% for 4 minutes, taking it out and drying it in an oven at 250 degrees for 20 minutes to obtain a PTFE prepreg with a solid content of 90%;
[0058] S12: After the PTFE semi-cured sheet prepared in step S11 is immersed in acryloylmorpholine (ACMO) monomer for 4 minutes, it is taken out and placed in an electron beam (EB) device for irradiation grafting (EB irradiation conditions: voltage 70KeV, dose 30KGy) to obtain a PTFE semi-cured sheet with high bonding strength.
[0059] A method for preparing a PTFE copper-clad laminate with high bonding strength, the method comprising the following steps:
[0060] S21: stack the four PTFE prepregs prepared in step S12 together, place a Luxembourg HFZ-B copper foil on each side, and place them in a vacuum high-temperature press for hot pressing (pressing parameters: vacuum degree greater than 720 mmHg, heating rate 2.0 degrees / minute, pressure during heating process 120 psi, maximum temperature 375 degrees, maximum pressure 400 psi, heat and pressure holding time 150 minutes);
[0061] S22: After the process of step S21 is completed, the temperature is naturally cooled to room temperature and then the pressure is released and taken out to obtain a PTFE copper-clad substrate with high bonding strength.
[0062] Comparative Example 1
[0063] A method for preparing a PTFE prepreg, the method comprising the following steps:
[0064] S11: placing an electronic grade glass fiber cloth with a specification of 106 in a PTFE emulsion with a solid content of 50% for 4 minutes, taking it out and drying it in an oven at 250 degrees for 20 minutes to obtain a PTFE prepreg with a solid content of 90%;
[0065] A method for preparing a PTFE copper-clad laminate, the method comprising the following steps:
[0066] S21: stack the four PTFE prepregs prepared in step S11 together, place a Luxembourg HFZ-B copper foil on each side, and place them in a vacuum high-temperature press for hot pressing (pressing parameters: vacuum degree greater than 720 mmHg, heating rate 2.0 degrees / minute, pressure during heating process 120 psi, maximum temperature 375 degrees, maximum pressure 400 psi, heat and pressure holding time 150 minutes);
[0067] S22: After the process of step S21 is completed, the temperature is lowered to room temperature and then the pressure is released and the substrate is taken out to obtain a PTFE copper-clad substrate.
[0068] Performance test results:
[0069] The PTFE copper-clad laminates prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were tested for peel strength, dielectric constant, dielectric loss, and high temperature resistance. The test results are shown in Table 1.
[0070] Table 1
[0071]
[0072]
[0073] From the test results in Table 1, we can see that:
[0074] The peel strength of the PTFE copper clad laminate prepared in Examples 1 to 3 of the present invention reaches 15 lb / inch, and the high temperature resistance performance T288 can reach 60 minutes, while maintaining an extremely low dielectric constant DK@10GHz (2.22) and an extremely low dielectric loss DF@10GHz (0.001); it is suitable for 5G communication fields such as the Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia.
[0075] The PTFE copper clad laminate prepared in Comparative Example 1 has an extremely low dielectric constant DK@10GHz (2.22) and an extremely low dielectric loss DF@10GHz (0.001), but its bonding strength with the copper foil is poor, resulting in poor high temperature resistance and unable to meet the performance requirements of high-frequency copper clad laminates for 5G communications.
[0076] This application uses electron beam (EB) irradiation technology to graft polar acrylate monomers onto the surface of PTFE prepregs, so that the low surface energy PTFE surface is grafted with polar groups, which greatly improves the bonding strength between the PTFE and copper foil, while not changing the dielectric properties of the PTFE material, thereby preparing PTFE prepregs and PTFE copper-clad laminates with high bonding strength. It is particularly suitable for 5G communication fields such as the Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia.
[0077] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A PTFE prepreg with high bonding strength, characterized in that: Polar acrylate monomers were grafted onto the surface of PTFE prepreg by electron beam irradiation technology; The polar acrylate monomer is selected from one or more of acrylate monomers having cyano, carboxyl, hydroxyl, acetylamino, alkoxy, amino, mercapto and heterocyclic structures.
2. The high-bonding PTFE prepreg according to claim 1, characterized in that: The polar acrylate monomer is one or more of a hydroxyalkyl acrylate monomer, an alkoxylated acrylate monomer and an acrylate monomer with a heterocyclic structure.
3. The method for preparing the high-bonding PTFE prepreg according to claim 1 or 2, characterized in that: Includes steps: S11. After the glass fiber is arranged in the PTFE emulsion and impregnated, it is taken out and dried at high temperature to obtain a PTFE prepreg; S12. The PTFE prepreg obtained in step S11 is impregnated with a polar acrylate monomer and subjected to electron beam irradiation grafting to obtain a PTFE prepreg with high bonding strength.
4. The preparation method according to claim 3, characterized in that: In step S11, the solid content of the PTFE emulsion is 40-60%; in step S11, the drying temperature is 220-280°C, and the drying time is 15-30 minutes; And / or, in step S11, the impregnation time is 3-5 minutes.
5. The preparation method according to claim 3, characterized in that: In step S12, the electron beam irradiation conditions are: voltage 10KeV-100KeV, dose 10KGy-100KGy; And / or, in step S12, the impregnation time is 3-5 minutes.
6. A method for preparing a copper-clad laminate based on the PTFE prepreg according to any one of claims 1 to 2, or the PTFE prepreg obtained by the preparation method according to any one of claims 3 to 5; characterized in that: Includes steps: S21. The multilayer PTFE prepreg is stacked together, copper foil is placed on top and bottom, and vacuum hot pressed; S22. After the process of step S21 is completed, the substrate is taken out after cooling and depressurizing to obtain a PTFE copper-clad substrate with high bonding strength.
7. The method for preparing a copper clad laminate according to claim 6, characterized in that: In step S21, four PTFE prepregs are stacked together, and a piece of RTF 1oz copper foil is placed on each of the top and bottom, and then placed in a vacuum high temperature press for hot pressing.
8. The method for preparing a copper clad laminate according to claim 6, characterized in that: In step S21, the hot pressing conditions are as follows: vacuum degree ≥ 720 mmHg, heating rate 1.5-3°C / min, pressure 80-150 psi during heating, maximum temperature 350-400°C, maximum pressure 350-450 psi, and heat and pressure holding time 120-180 minutes.
9. A copper clad laminate obtained by the preparation method according to any one of claims 6 to 8.
10. Application of the prepreg according to any one of claims 1 to 2, or the copper clad laminate according to claim 9 in the field of 5G communications, characterized in that: Including but not limited to applications in the fields of Internet of Things, Internet of Vehicles, artificial intelligence, and interactive multimedia.